ACTORS, SCREENS AND VIRTUAL REALITY: PIRANDELLO’S THEATRE ON THE STAGE OF THE NEW MILLENNIUM - Ranzini, Paola (ΠΑΡΑΒΑΣΙΣ/PARABASIS, 2025)
This contribution studies some of the recent staging initiatives of Pirandello’s theatre. With The six characters in search of an author (1921) this author has completely renovated the European theatre. Pirandello theatre’s modernity is such that –as evidenced by the shows studied, which are arranged on a chronology ranging from the 1970s to 2021, to better understand it and to give substance to the philosophical questions that animate it– filmmakers often resort to new tools and languages. The article covers scenes that use screens, television, cinema and virtual reality to interpret Pirandello and stage his creations. However, these experiments are not random since they are based on statements taken from the works of Pirandello himself…